Analisis Penyebab Keterlambatan Pengiriman Barang Pada Pos Express Menggunakan Metode Six Sigma - Charles Marsello Hersanto; Nur Tri Ramadhanti Adiningrum; Dani Leonidas Sumarna (LOGISTIK, 2023)
The speed and accuracy of the distribution of goods is an important factor that is continuously driven by shipping service companies. Service quality has a very important impact on determining the quality of the company. Pos Indonesia has a next day (H+1) goods delivery service product under the name Pos Express. However, in cases that occur in the field, Pos Express has problems in shipping goods in the form of delays in delivery. These problems have an impact on the quality of services provided by Pos Indonesia to its consumers. The purpose of this study is to analyze the causes of delays in delivery of goods and provide recommendations for improvements to Pos Express products. The method used in this research is Six Sigma with the DMAIC approach. The results of this study are delivery delays that are influenced by human error factors (counter clerk errors, inexperienced couriers, and sorting officer errors) which can be overcome by providing guidance and imposing sanctions on related workers, less prime vehicle conditions which can be overcome by periodic checking just before leaving, transportation planning errors that can be overcome through re-planning by considering the vehicle's load capacity and the number of goods on hand, and traffic jams that can be overcome by determining delivery routes and delivery times that are far from heavy traffic flows.